OCULAR INVOLVEMENT IN SNAKEBITE PATIENT: A CASE TO REMEMBER: Poster Presentation - Case Report - General practitioner - Novianti; Elisa Yopitasari (Majalah Oftalmologi Indonesia, 2023)
Introduction : Snake bite cases in Indonesia are not rare with mild to catastrophic consequences on the bitten subject due to its hemolytic and neurotoxic effects. This case represents a rare ocular neurotoxic effect of snake’s venom that cause binocular diplopia and ptosis in a child. Case Illustration : A 9 year-old boy was consulted to ophthalmologist with chief complaint of binocular diplopia. He was hospitalized after being bitten by a snake on his right hand and had an episode of delirious state. Ophthalmologic examination revealed ptosis and exotropia of his left eye in primary position. Further examination of anterior and posterior segments showed good results. His visual acuity was unaffected. Intravenous antivenom was administered and the bite wound was taken care. The boy was discharged from the hospital with a good general condition but still an opthalmoplegia. After a week of follow up the diplopia diminished and his ocular motility was recovered. Discussion : Ocular manifestations in snake bite case might be missed because of delirious state of the patients. Snake venom can cause ptosis and ophthalmoplegia (neurotoxic) along with uveitis, optic neuritis, central retinal artery occlusion or vitreous and retina hemorrhage due to its hemolytic effect. Time interval between the bite and treatment is one of crucial factor that indicate the patient’s prognosis. Conclusion : Thorough examination of anterior to posterior ocular segments is needed in every snake bitten patients to rule out any further ocular complication. An early administration of intravenous antivenom is still a mandatory.